Vagueza e indeterminação na noção de história de Arendt - Bortolotti, Ricardo Gião [UNESP] (My University, 2012)
The purpose of this paper is to present the thought of Hannah Arendt on the historical narrativa, as the reading of theories of cognition and the sign of Peirce. It is not categorial parallelism, but to highlight some approximation in order to conceive the thought and language. For both, communication is important in the formation of your thoughts. While one has broader interests, the other directs its efforts to human society, politics and history. However, both authors agree on the fallible nature o four opinions, and reject the traditional philosophies, advocates of transcendental schemes, which are imposed, silencing the experience, the source o four opinions. The proposal, to seek the experience, the origino f opinions, ou interpretations, excluding transcental rules, but the community is what gives the character of the narrative indeterminacy. They do not escape from the temporal and social factors. Therefore, are subject to what gives them legitimacy, ie, freedom.

O objetivo deste artigo é expor o pensamento de Hannah Arendt sobre a narrativa histórica, conforme a leitura das teorias da cognição e do signo de Peirce. Não se trata de paralelismo categórico, mas de realçar certa aproximação no modo de conceber o pensamento e a linguagem. Para ambos, a comunicação é fator importante na constituição de seus pensamentos. Enquanto um possui interesses mais amplos, o outro dirige seus esforços para o convívio humano, para a política e a história. No entanto, os dois autores estão de acordo quanto ao caráter falível de nossas opiniões, além de rejeitarem as filosofias tradicionais, defensoras de esquemas transcendentais, os quais são impostos, calando a experiência, fonte de nossas opiniões. Essa proposta, de buscar na experiência a origem das opiniões, ou interpretações, sem contar com regras transcendentais, mas com a comunidade, é que confere o caráter de indeterminação às narrativas. Elas não escapam dos fatores temporais e sociais. Portanto, estão sujeitas àquilo que lhes confere legitimidade, ou seja, à liberdade.
Vagueness and indeterminacy in arendt’s concept of history
Keywords: Thought; Sign; Narrativa; History; Pensamento; Signo; Narrativa; História